2018
DOI: 10.3389/fmicb.2018.00153
|View full text |Cite
|
Sign up to set email alerts
|

Growth Rate and Biofilm Formation Ability of Clinical and Laboratory-Evolved Colistin-Resistant Strains of Acinetobacter baumannii

Abstract: Two different mechanisms of resistance to colistin in Acinetobacter baumannii have been described. The first involves the total loss of lipopolysaccharide (LPS) due to mutations in the lpxACD operon, which is involved in the lipid A biosynthesis pathway. The second entails the addition of ethanolamine to the lipid A of the LPS resulting from mutations in the PmrAB two-component system. To evaluate the impact of colistin resistance-associated mutations on antimicrobial resistance and virulence properties, four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…The high emergence rates of multidrug resistance (MDR) and extensively drug resistance (XDR) among A. baumannii isolates have led them to be considered as one of the top seven pathogens posing threats to medical and health systems (1,2). In addition to antibiotic resistance, biofilm formation is another characteristic leading to the survival of A. baumannii in the presence of antibiotics and high stresses (1)(2)(3). It was revealed that the difference in biofilm formation capacity among international clonal (IC) types of A. baumannii could affect the spreading of this microorganism (4).…”
Section: Introductionmentioning
confidence: 99%
“…The high emergence rates of multidrug resistance (MDR) and extensively drug resistance (XDR) among A. baumannii isolates have led them to be considered as one of the top seven pathogens posing threats to medical and health systems (1,2). In addition to antibiotic resistance, biofilm formation is another characteristic leading to the survival of A. baumannii in the presence of antibiotics and high stresses (1)(2)(3). It was revealed that the difference in biofilm formation capacity among international clonal (IC) types of A. baumannii could affect the spreading of this microorganism (4).…”
Section: Introductionmentioning
confidence: 99%
“…Pilus biosynthesis is important during the initial biofilm formation period, and this process depends on the csuA/BABCDE system (Gaddy & Actis, 2009;Longo, Vuotto, & Donelli, 2014). Biofilm rates (Farshadzadeh et al, 2018). Zea et al (2017) reported that E. coli cells in space accounted for 37% of the volume of the control group.…”
Section: Hensley (2010) Reported Similar Results Showing That Clinicmentioning
confidence: 99%
“…Biofilm formation in A. baumannii requires expression of biofilm‐related genes, such as csuA/B/D . Additionally, changes in the biofilm formation ability are probably associated with changes in growth rates (Farshadzadeh et al, ). Zea et al () reported that E. coli cells in space accounted for 37% of the volume of the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilm-related outer membrane lipoprotein (pgaB) was found to be upregulated in colistin resistant strains (10). However, another study showed that mutations involved in colistin resistance phenotype downregulate the expression of biofilm-associated genes of colistin-resistant isolates (11).…”
mentioning
confidence: 99%